Ash transformation mechanism during combustion of rice husk and rice straw. (1st January 2022) - Beidaghy Dizaji, Hossein; Zeng, Thomas; Hölzig, Hieronymus; Bauer, Jens; Klöß, Gert; Enke, Dirk
Graphical abstract: This graphic shows the link between ash melting behaviour and ash quality in silica-rich biomass combustion. Highlights: Critical ash forming elements influence atomic structure of silica-rich biomass ash. FactSage calculations can predict ash melting in silica-rich biomass combustion. Quantitative XRD phase analysis is completely in line with the simulation. Chemical pre-treatment is an effective method to mitigate ash melting. Above than the crystallinity threshold, silica-rich biomass ashes are non-porous. Abstract: Biomass is an alternative energy resource to fossil fuels because of its potential to reduce greenhouse gas emissions. However, ash-related problems are serious obstacles for this development, especially for the use in combustion plants. Thus, design and operation of biomass boilers require detailed understanding of ash transformation reactions during thermochemical conversion. To evaluate ash transformation in silica-rich biomass fuels, rice husk and rice straw were selected because of their abundance, limited utilization conflicts with the food sector, as well as their potential in both energy and material applications. This paper reveals ash transformation mechanisms relevant for the ash melting behaviour of silica-rich biomass fuels considering chemical and phase composition of the ashes. In this regard, several advanced spectroscopic methods and diffractometry were employed to characterize the materials. The ash transformation reactions and the viscosity were simulated using thermodynamic equilibrium calculations and a slag viscosity modeling toolbox. The results illustrate the impact of impurities on the atomic structure of the silica resulting in an altered ash melting behaviour and viscosity of the silica-rich ashes. Chemical water washing, acid leaching, and blending of rice straw with rice husk strongly influenced the chemical composition of the ashes and improved ash melting behaviour. The analysis also revealed the correlation between the crystalline fraction and the porosity in silica-rich biomass ashes, as well as a crystallinity threshold. These findings are highly relevant for future investigations in boiler designs and production of biogenic silica for material applications.